Harmonizing corporate venturing dimensions and its characteristics: a systematic analysis - Nils Dall; Orestis Terzidis; Leon Krooß (Management Review Quarterly, 2024)
Abstract The research literature on Corporate Venturing (CV) has increased over the last few years. While research mainly focuses on analyzing one single CV dimension (e.g. Ambidexterity, etc.) or the interplay between selected dimensions, rarely does research cover and explain all CV dimensions and their characteristics holistically. This paper analyzes the status quo of different CV dimensions and their characteristics. To do so, we identified 100 studies we first used to perform a bibliometric analysis. After that, we executed a conceptual systematic literature review (SLR), updating and extending an existing research paper written by Gutmann (Manag Rev Q 69(2):121–157, 2018). The bibliometric analysis results help objectively evaluate and describe the research landscape and point out leading countries, main keywords, main cited papers, and main research clusters of our CV research. We discovered three new dimensions within our SLR: Relatedness, Time Horizon, and Development Stage. In addition, we show new findings within the 7 CV dimensions described by the existing research paper. Even though the characteristics within each dimension have, to some extent, developed significantly over time, each of the dimensions described in this paper contains substantial new knowledge. e.g. previously the dimension “Link to the corporate firm” mainly covered operational and structural linkages. However, we distinguish these linkages between operational and strategic autonomy.
Additional information: G24;L1;L21;L26;M10
Keywords: 330; Corporate venturing; Corporate venturing dimensions; Innovation management; Entrepreneurship; Systematic literature review; Bibliometric analysis